From innovation to integration: a global mixed-methods study of VR, metaverse, and 3D simulation in healthcare training and clinical setting - Tomita, Daisuke; Abdelhakim, Mohamed; Bartkova, Julia; Gulsum, Akkoyun; Sato, Atsushi; Alshiblan Alotaibi, Naif H.; Aboulhassan, Mamdouh; Dongcai, Li; Tomita, Yumiko (Frontiers in Digital Health, 2025)
BackgroundImmersive technologies in healthcare including virtual reality (VR), metaverse platforms, and 3D display technology are transforming global healthcare by improving medical education, advancing surgical training, enhancing patient preparedness, and facilitating remote collaboration. Adoption varies regionally due to infrastructure, cost, and digital literacy gaps. This study examined their impact on healthcare training and delivery outcomes and identified key integration barriers.MethodsThis mixed-methods instructional-integration study spanning four regions, Japan, the Middle East and North Africa, China, and the United States, utilized pre- and post-training surveys. Participant confidence in using immersive technologies was rated on a 5-point Likert scale. Paired t-tests determined significance. Thematic analysis of qualitative data (open-ended responses) identified key benefits and implementation challenges.ResultsOf 350 healthcare professionals, 300 completed both surveys. Confidence improved significantly across all technologies: VR simulators (2.8–4.2), metaverse platforms (3.1–4.0), and 3D display systems (3.2–4.3), all p < 0.05. Regional trends were consistently positive, with favorable outcomes in surgical precision and spatial understanding (Cairo University, Al Faisal University). Thematic analysis cited expense (62%), limited infrastructure (56%), and need for context-specific training (49%) as key barriers; 88% of participants reported increased willingness towards applying immersive technology in healthcare settings.DiscussionImmersive technologies significantly enhance medical education and procedural training, demonstrating cross-regional applicability. Favorable feedback-based gains in user confidence underscore their transformative potential. Equitable adoption requires tackling systemic barriers through strategic investment, localized customization, and international collaboration. These findings offer actionable insights to inform policy and program development for digital healthcare transformation.